The Design and Use of Tungsten Coated TZM Molybdenum Tile Inserts in the DIII-D Tokamak Divertor. (17th November 2017) - Holtrop, K.; Buchenauer, D.; Chrobak, C.; Murphy, C.; Nygren, R.; Unterberg, E.; Zach, M.
Abstract: Future tokamak devices are envisioned to utilize a high-Z metal divertor with tungsten as the leading candidate. However, tokamak experiments with tungsten divertors have seen significant detrimental effects on plasma performance. The DIII-D tokamak presently has carbon as the plasma facing surface but to study the effect of tungsten on the plasma and its migration around the vessel, two toroidal rows of carbon tiles in the divertor region were modified with high-Z metal inserts, composed of a molybdenum alloy (TZM) coated with tungsten. A dedicated two week experimental campaign was run with the high-Z metal inserts. One row was coated with tungsten containing naturally occurring levels of isotopes. The second row was coated with tungsten where the isotope 182 W was enhanced from the natural level of 26% up to greater than 90%. The different isotopic concentrations enabled the experiment to differentiate between the two different sources of metal migration from the divertor. Various coating methods were explored for the deposition of the tungsten coating, including chemical vapor deposition, electroplating, vacuum plasma spray, and electron beam physical vapor deposition. The coatings were tested to see if they were robust enough to act as a divertor target for the experiment. Tests included cyclic thermal heating using a high power laser and high-fluence deuterium plasma bombardment. The issues associate with the design of the inserts (tile installation, thermal stress, arcing, leading edges, surface preparation, etc.), are reviewed. The results of the tests used to select the coating method and preliminary experimental observations are presented.